Analysis of Liver Function on Leprosy Patient with Multidrug Therapy in Haji Adam Malik General Hospital Medan from January until December 2017 - Darmi, Mila; Lubis, Ramona Dumasari (Open Access Macedonian Journal of Medical Sciences, 2020)
Leprosy is a chronic progressive granulomatous disease that caused by Mycobacterium leprae, an intracellular obligate bacteria. Leprosy can be treated using multidrug therapy (MDT) that can be associated with hepatotoxicity as their side effects. We included 14 patients that were all diagnosed with multibacillary leprosy, but with four drops out persons. Liver function evaluations before MDT were in the normal range. After 1st, 2nd, and 3rd months of MDT, liver function test in research subjects also in the normal range even though there is variation in this value. There is a risk of hepatotoxicity of MDT; therefore, liver function test should be done periodically for early detection of any liver dysfunction.